2020
DOI: 10.1002/cpsc.109
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Patient‐Derived Head and Neck, Oral, and Esophageal Cancer Organoids

Abstract: Esophageal cancers comprise adenocarcinoma and squamous cell carcinoma, two distinct histologic subtypes. Both are difficult to treat and amongst the deadliest human malignancies. We describe protocols to initiate, grow, passage and characterize patient-derived organoids (PDO) of esophageal cancers as well as squamous cell carcinomas of oral/head-and-neck and anal origin. Formed rapidly (< 14 days) from a single cell suspension embedded in basement membrane matrix, esophageal cancer PDO recapitulate the histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 42 publications
0
67
0
1
Order By: Relevance
“…Three-dimensional (3D) tumor organoid models have been consistently shown to faithfully recapitulate features of the tumor of origin in terms of cell differentiation, heterogeneity, histoarchitecture, and clinical drug response [ 29 32 ]. Thus, there is increasing interest in developing tumor organoid models for drug development and personalized medicine applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional (3D) tumor organoid models have been consistently shown to faithfully recapitulate features of the tumor of origin in terms of cell differentiation, heterogeneity, histoarchitecture, and clinical drug response [ 29 32 ]. Thus, there is increasing interest in developing tumor organoid models for drug development and personalized medicine applications.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that patient-derived organoids could accurately predict patient responses to therapy, with 100% sensitivity and 93% specificity [ 37 ]. While establishing patient-derived xenografts is costly and time-consuming, in vitro 3D organoids derived from primary cancers can be established rapidly, with successful passage within 10–14 days of in vitro growth and with >80% efficiency [ 29 ]. Thus far, we have cultivated patient-derived organoids from normal oral epithelium and OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 7, 2020. ; https://doi.org/10.1101/2020.07.03.20145854 doi: medRxiv preprint costly and time-consuming, in vitro 3D organoids derived from primary cancers can be established rapidly, with successful passage within 10-14 days of in vitro growth and with >80% efficiency [35]. Thus far, we have cultivated patient-derived organoids from normal oral epithelium and OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The single cell suspension (4×10 5 /ml) was mixed with Matrigel (Corning, Corning, NY) and 2×10 4 cells in 50 μl of Matrigel were seeded into the 24-well plates. Organoids were grown for 10-14 days at 37°C in a humidified atmosphere of 5% CO2 as previously described [19]. Under an inverted phase-contrast microscope, growing organoids were observed and photomicrographed to determine their number and size.…”
Section: Htert Expression Analysesmentioning
confidence: 99%
See 1 more Smart Citation